Stock overreaction and financial bubbles: evidence from Malaysia - Ali, Norli; Md Nassir, Annuar; Hassan, Taufiq; Zainal Abidin, Sazali (EuroJournals Publishing, 2009)
This paper attempts to seek linkage between stock overreaction behaviour and financial bubbles in the Malaysian stock market. Monthly data over a period between January 1987 and December 2006 shows no clear evidence of stock overreaction behavior in the market. However, when the study split the analysis into two sub-periods, evidence of stock overreaction behaviour becomes significant in the pre-crisis sub-period, but there is no significant evidence of financial bubbles in the same sub-period. During the post crisis, evidence of stock overreaction seems to diminish, and evidence of financial bubbles however, is observed in the period. This study believes that evidence of bubbles observed in the Malaysian stock market in the post crisis period is due to stock overreaction that took place in the market prior to the crisis.